People's Economic Bank to the Capital Market: Challenges and Innovations - Debrina Rahmawati (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The expansion of the scope of People's Economic Bank (BPR)s to enter the capital market is new in Indonesia. The legal arrangements are not yet fully regulated. Several obstacles are experienced by BPRs towards the capital market. Therefore, innovations are needed that can make BPRs enter the capital market by applying some existing legal arrangements even though they are not specifically regulating BPRs. The purpose of this study is to determine the barriers and innovations in the framework of BPR towards the capital market. Normative legal method by taking a statutory and conceptual approach. There are several challenges BPR in heading to the capital market. The answer to these challenges is innovation. The existence of innovations that can be applied to BPR in order to go to the capital market can be seen from the legal arrangements that already exist in other fields but can be applied in the BPR. BPR experiences several obstacles, including (1) Changes from closed to public LLC must go through several processes before heading to the capital market, (2) Changes in share ownership that can determine company policy and (3) Capital fulfillment factors required by the capital market. The innovations made are (1) the fulfillment of corporate governance, (2) Share ownership arrangements that can still be held by families with (a) The form of holding companies and subsidiaries with certain ownership arrangements, and (b) Applying dual class shares, (3) BPRs that have not met the capital requirements can enter through the OTC market with reporting obligations in each securities transaction.